Using Microphone Arrays to Detect Moving Vehicle Velocity - Ramón PERAL-ORTS; Emilio VELASCO-SANCHEZ; Nuria CAMPILLO-DAVÓ; Hector CAMPELLO-VICENTE (Archives of Acoustics, 2013)
The noise of motor vehicles is one of the most important problems as regards to pollution on main roads. However, this unpleasant characteristic could be used to determine vehicle speed by external observers. Building on this idea, the present study investigates the capabilities of a microphone array system to identify the position and velocity of a vehicle travelling on a previously established route. Such linear microphone array has been formed by a reduced number of microphones working at medium frequencies as compared to industrial microphone arrays built for location purposes, and operates with a processing algorithm that ultimately identifies the noise source location and reduces the error in velocity estimation.